THE EXPRESSION OF NFATC1 IS MORE PREDOMINANT IN TRIPLE NEGATIVE BREAST CARCINOMA PATIENTS - Riana Sari Puspita Rasyid; Krisna Murti; Zen Hafy (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Breast carcinoma is the most common malignancy among women in developed and developing countries. Invasive breast carcinomas are classified into 4 subtypes i.e. luminal A and B, human epidermal growth factor receptor 2 (HER2)-enriched and triple negative, the latter has the worst prognosis. Nuclear factor of activated T cell (NFATc)1 is an important transcription factor in malignant transformation and progression. Therefore, NFATc1 expression may determine prognosis of breast carcinoma. This study aimed to determine the roles of NFATc1 inbreast carcinoma progression. Materials and Methods Fifty-two paraffin blocks were selected and prepared to assess NFATc1 expression by immunohistochemistry. These data were taken from medical records: i.e. molecular classification, patient age, tumor size, lymphovascular invasion and grade of tumor were recorded. Results: Positive NFATc1 expression was observed in 4 samples i.e. in the nuclei of luminal A (1 out of 12; 8.8%), luminal B (1 out of 15; 6.7%), and triple negative (2 out of 12; 16.7%), but no NFATc1 expression was detected in HER2-enriched samples. Clinicopathologically, more of these patients were in the fifth decade (38.5%), with larger tumor size (?2 cm; 90%), lymphovascular invasion positive (80.8%), and high degree (3; 59.6%). Conclusion: NFATc1 expression is more predominant in triple negative breast carcinoma.